우리나라에서 최근(1982 ~ 2020) 발생한 여름철 급성가뭄의 특성 및 변화에 대한 연구 - 김경민(Kim, Kyungmin); 우성호(Woo, Sung-Ho); 백은혁(Baek, Eun-Hyuk); 정지훈(Jeong, Jee-Hoon) (한국기후변화학회지, 2022)
A flash drought is a rapidly evolving drought, unlike general meteorological droughts that develop over months to years due to persistent precipitation deficits. This study investigated the characteristics of summertime flash droughts in South Korea for the period of 1982 ~ 2020. Flash droughts can be classified into heatwave flash droughts and precipitation deficit flash droughts, with the former occurring most frequently in South Korea. Both the occurrence and duration of flash droughts increased during the analysis period, especially heatwave flash droughts. Composite analysis results of reanalysis dataset and land surface model simulation revealed that large-scale anticyclonic atmospheric circulation and positive temperature anomalies contribute to increased evapotranspiration and reduced soil moisture, which lead to flash droughts in South Korea. In the summer of 2016 and 2018, when flash droughts occurred most frequently with record-breaking heatwaves, these characteristics were prevalent. Land-atmosphere interactions associated with the anticyclonic circulation might influence the development of summer heatwave flash droughts in South Korea. KCI Citation Count: 0